Trash for Cash Programme supports UMPSA Sustainability Agenda - Suhaidah, Hussain; Puteri Fadzline, Muhamad Tamyez (UMPSA, 2024)
GAMBANG, 11 January 2024 - Universities are hubs for knowledge and innovation. However, with a large amount of waste generated within universities, it becomes the university's obligation to enhance UMPSA community's commitment to minimizing waste while preserving the environment.